PELAKSANAAN PENGELOLAAN SIMPANAN ANGGOTA OLEH KOPERASI SIMPAN PINJAM JASA PEKALONGAN - Aditya Mulya Prihatna, Srie Wiletno*, Hendro Saptono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
One of the activities of Cooperatives is to gather funds from members. Activities to gather funds from community has a big risk. Many members of the misappropriation of funds make an image of cooperative becomes low and the loss of confidence of members. Required the implementation of appropriate management of Member deposits with values of cooperatives to avoid failure on cooperatives. The emergence of obstacles in the management of deposits member becomes a challenge for cooperatives to be able to get it done and keep the continuity of the cooperative.